Digitization as Manifested in Travel: An Overview - Sebastine, Kiron Susan Joseph; Muraleedharan K, Sreenath (International Journal of Psychosocial Rehabilitation, 2020)
Travel acknowledges the constant fluidity of the cognitive entities; the rejection of the familiar and the embrace of the unfamiliar. It is essential to explore the myriad ways through which digitization has penetrated the arena of Cultural Studies employing travel as a medium of intervention. In travel, cultures address each other, communicate and negotiate their perspectives sustained by digitization. The power relations as well as the history and socio-political perceptions of the participant cultures endorses a transmission that necessitates the emphasis of digitization in travel and its interrelated subfields. Travel that is reinforced by digitization holds the most common ground in our culture for the customary conversation which is arguably the most prevalent interaction of an individual. Digitization has leveraged the power of travel as well as its quotidian requirements. This paper explores the metamorphosis encountered by travel owing to digitization. The paper further acknowledges the role played out by travel in the formulation and sustenance of identity in a digital society.